Potato and sweetpotato breeding at the International Potato Center: approaches, outcomes and the way forward - Hannele Lindqvist-Kreuze; Merideth Bonierbale; Wolfgang J. Grüneberg; Thiago Mendes; Bert De Boeck; Hugo Campos (Theoretical and Applied Genetics, 2024)
Root and tuber crop breeding is at the front and center of CIP’s science program, which seeks to develop and disseminate sustainable agri-food technologies, information and practices to serve objectives including poverty alleviation, income generation, food security and the sustainable use of natural resources. CIP was established in 1971 in Peru, which is part of potato’s center of origin and diversity, with an initial mandate on potato and expanding to include sweetpotato in 1986. Potato and sweetpotato are among the top 10 most consumed food staples globally and provide some of the most affordable sources of energy and vital nutrients. Sweetpotato plays a key role in securing food for many households in Africa and South Asia, while potato is important worldwide. Both crops grow in a range of conditions with relatively few inputs and simple agronomic techniques. Potato is adapted to the cooler environments, while sweetpotato grows well in hot climates, and hence, the two crops complement each other. Germplasm enhancement (pre-breeding), the development of new varieties and building capacity for breeding and variety testing in changing climates with emphasis on adaptation, resistance, nutritional quality and resource-use efficiency are CIP’s central activities with significant benefits to the poor. Investments in potato and sweetpotato breeding and allied disciplines at CIP have resulted in the release of many varieties some of which have had documented impact in the release countries. Partnership with diverse types of organizations has been key to the centers way of working toward improving livelihoods through crop production in the global South.

PL-4 (CIP596131.4): an Improved Potato Haploid Inducer - Benny Ordoñez; Monica Santayana; Mariela Aponte; Isabelle M. Henry; Luca Comai; Raúl Eyzaguirre; Hannele Lindqvist-Kreuze; Merideth Bonierbale (American Journal of Potato Research, 2021)
Dihaploid production from elite tetraploid cultivars is key to both traditional and novel breeding approaches that seek to simplify potato genetics. For this purpose, efficient and widely compatible haploid inducers (HIs) are needed. We compared PL-4, a new HI developed at the International Potato Center, to known HIs IvP101 and IvP35. By pollination of elite tetraploid breeding lines, we showed that PL-4 performed significantly better and had a homogeneous response regardless of the genetic background of the pistillate parents, on the most important efficiency traits—number of dihaploids per 100 fruits and haploid induction rate. Moreover, PL-4 exhibited a reduced proportion of hybrid seeds, a convenient trait for efficient screening. In this context, we recommend PL-4 as an enhanced HI for the potato breeding community.

The Nutritional Contribution of Potato Varietal Diversity in Andean Food Systems: a Case Study - Stef de Haan; Gabriela Burgos; Reyna Liria; Flor Rodriguez; Hilary M. Creed-Kanashiro; Merideth Bonierbale (American Journal of Potato Research, 2019)

Yield and Physiological Response of Potatoes Indicate Different Strategies to Cope with Drought Stress and Nitrogen Fertilization - David Saravia; Evelyn Roxana Farfán-Vignolo; Raymundo Gutiérrez; Felipe De Mendiburu; Roland Schafleitner; Merideth Bonierbale; M. Awais Khan (American Journal of Potato Research, 2016)

Multiple QTLs Linked to Agro-Morphological and Physiological Traits Related to Drought Tolerance in Potato - M. Awais Khan; David Saravia; Susan Munive; Flavio Lozano; Evelyn Farfan; Raul Eyzaguirre; Merideth Bonierbale (Plant Molecular Biology Reporter, 2015)

SSR and e-PCR Provide a Bridge Between Genetic Map and Genome Sequence of Potato for Marker Development in Target QTL Region - Jingcai Li; Conghua Xie; Zhendong Tian; Hannele Lindqvist-Kreuze; Merideth Bonierbale; Jun Liu (American Journal of Potato Research, 2015)

Early generation in vitro assay to identify potato populations and clones tolerant to heat - M. Awais Khan; Susan Munive; Merideth Bonierbale (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Heritability of Yield Components Under Irrigated and Drought Conditions in Andigenum Potatoes - Rolando Cabello; Philippe Monneveux; Merideth Bonierbale; M. Awais Khan (American Journal of Potato Research, 2014)

An RGA-Derived SCAR Marker Linked to PLRV Resistance from Solanum tuberosum ssp. andigena - Elisa Mihovilovich; Mariela Aponte; Hannele Lindqvist-Kreuze; Merideth Bonierbale (Plant Molecular Biology Reporter, 2014)

Comparison of yield based drought tolerance indices in improved varieties, genetic stocks and landraces of potato (Solanum tuberosum L.) - Rolando Cabello; Philippe Monneveux; Felipe De Mendiburu; Merideth Bonierbale (Euphytica, 2013)

Conditional QTL underlying resistance to late blight in a diploid potato population - Jingcai Li; Hannele Lindqvist-Kreuze; Zhendong Tian; Jun Liu; Botao Song; Juan Landeo; Leticia Portal; Manuel Gastelo; Julio Frisancho; Laura Sanchez; Dennis Meijer; Conghua Xie; et al. (Theoretical and Applied Genetics, 2012)

Carbohydrate metabolism and cell protection mechanisms differentiate drought tolerance and sensitivity in advanced potato clones (Solanum tuberosum L.) - Sylvain Legay; Isabelle Lefèvre; Didier Lamoureux; Carolina Barreda; Rosalina Tincopa Luz; Raymundo Gutierrez; Roberto Quiroz; Lucien Hoffmann; Jean-François Hausman; Merideth Bonierbale; Danièle Evers; Roland Schafleitner (Functional & Integrative Genomics, 2011)

Quantitative resistance to late blight from Solanum berthaultii cosegregates with R Pi-ber : insights in stability through isolates and environment - Gilda Rauscher; Ivan Simko; Hilary Mayton; Merideth Bonierbale; Christine D. Smart; Niklaus J. Grünwald; Andrew Greenland; William E. Fry (Theoretical and Applied Genetics, 2010)

Proline accumulation and real time PCR expression analysis of genes encoding enzymes of proline metabolism in relation to drought tolerance in Andean potato - Roland Schafleitner; Amélie Gaudin; Raymundo Oscar Gutierrez Rosales; Carlos Alberto Alvarado Aliaga; Merideth Bonierbale (Acta Physiologiae Plantarum, 2007)

Field Screening for Variation of Drought Tolerance in Solanum tuberosum L. by Agronomical, Physiological and Genetic Analysis - Roland Schafleitner; Raymundo Gutierrez; Ricardo Espino; Amelie Gaudin; José Pérez; Mariano Martínez; Alejandro Domínguez; Luz Tincopa; Carlos Alvarado; Giannina Numberto; Merideth Bonierbale (Potato Research, 2007)